Pengaruh Motivasi, Ekspektasi Pendapatan dan Pemahaman Akuntansi Terhadap Minat Berwirausaha Mahasiswa Sarjana Akuntansi FEB UNUD - Kadek Pandi Juliadi; Ni Ketut Lely Aryani Merkusiwati (Journal Of Business, Finance, and Economics (JBFE), 2025)
Entrepreneurial interest is an innate desire to start one's own business, then the principles, skills, and actions of an entrepreneur in facing difficulties in pursuing opportunities, risks, and rewards are the subjects of entrepreneurship. Motives, income expectations, and familiarity with accounting are some of the variables that influence a person's likelihood of pursuing entrepreneurial interests. The purpose of this study was to determine the relationship between accounting knowledge, accounting motivation, and income expectations with the level of entrepreneurial interest among undergraduate accounting students at the Faculty of Economics and Business, Udayana University. A total of 165 participants in this study were selected using a purposive sampling technique. We conducted a multiple linear regression study. Factors such as income expectations and motivation, not accounting expertise, influence students' interest in starting their own companies, according to the study. The findings of this study can provide an overview of the level of entrepreneurial curiosity among students. To help reduce the unemployment rate among undergraduate graduates, the findings of this study can be used by the FEB Unud campus to disseminate information about entrepreneurship in an effort to arouse students' interest and inspire them to pursue it.